ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BANYAK PENGANGGURAN DI DESA LAGADAR - Ageng saepudin kanda S; Manifa siti nafiah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. Indonesia, as a developing country with a large population, has abundant labor potential. However, the population's opportunity to work can become high if it is not balanced with adequate employment growth. Unemployment is not only a macroeconomic problem that directly affects human survival, but also affects living standards. Therefore, the aim of this research is to find out how much impact inflation growth has on the unemployment rate and also to find out what factors cause high levels of unemployment. This research uses a qualitative research method, where data is collected through direct observation as the main data source. The results of this research are the low level of education in the Lagadar Village community which makes it difficult to get a job. Apart from that, economic factors and poverty are also factors that cause people not to continue their education, which ultimately results in many young people being unemployed. Keywords: Unemployment, Society, economy, factors.